1998
DOI: 10.1128/mcb.18.7.4165
|View full text |Cite
|
Sign up to set email alerts
|

The Capacity of Polyomavirus Enhancer Binding Protein 2αB (AML1/Cbfa2) To Stimulate Polyomavirus DNA Replication Is Related to Its Affinity for the Nuclear Matrix

Abstract: The nuclear matrix is thought to play an important role in the DNA replication of eukaryotic cells, although direct evidence for such a role is still lacking. A nuclear matrix-associated transcription factor, polyomavirus (Py) enhancer binding protein 2␣B1 (PEBP2␣B1) (AML1/Cbfa2), was found to stimulate Py replication through its cognate binding site. The minimal replication activation domain (RAD) was identified between amino acid (aa) 302 and aa 371 by using a fusion protein containing the GAL4 DNA binding d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 58 publications
2
39
1
Order By: Relevance
“…The leukemia-related AML1 and promyelocytic leukemia proteins have previously been identified as nuclear matrixassociated factors, consistent with recent findings by others (23,34). Here we report that AML1͞ETO and ETO are also nuclear matrix associated.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The leukemia-related AML1 and promyelocytic leukemia proteins have previously been identified as nuclear matrixassociated factors, consistent with recent findings by others (23,34). Here we report that AML1͞ETO and ETO are also nuclear matrix associated.…”
Section: Discussionsupporting
confidence: 93%
“…The normal form of the AML1 protein has an N-terminal region containing a runt homology DNA-binding domain (27) and a multifunctional C-terminal region that supports transactivation, repression, and intranuclear targeting (28)(29)(30)(31)(32)(33)(34). Alternative splicing of the AML1 gene can generate several protein isoforms.…”
mentioning
confidence: 99%
“…The region between residues 1 and 49 prevents the Runt domain from interacting with either PEBP2␤ or DNA. transcription inhibition domain, TE1, 2 and 3: transcription activation elements, NLS: nuclear localization signal, NRDBn and NRDBc: negative regulatory region for DNA binding, located at N-terminal, and C-terminal sides, respectively, NRHn and NRHc: negative regulatory region for heterodimerization, located at N-terminal and C-terminal sides, respectively, Nuclear Matrix Association: the region tightly associated with nuclear matrix (Chen et al 1998), PPPY: so called PY motif to which WW-domain containing Yes associated protein (YAP) binds (Yagi et al 1999), Smads 1, 2, 3, 5: the region responsible for interaction with Smad1, Smad2, Smad3 and Smad5 (Hanai et al 1999), p300: the region responsible for interaction with p300 (Kitabayashi et al 1998a), Ear-2: the region responsible for interaction with Ear-2 (Ahn et al 1998), MAPK: two serine residues phosphorylated by MAP kinase (Tanaka et al 1996).…”
Section: Autoinhibition Of Dna Binding and Heterodimerizationmentioning
confidence: 99%
“…The nuclear matrix seems to be particularly important in this respect. We observed that the initiation of polyomavirus (Py) DNA replication takes place in the nuclear matrix and requires transcription factors including ␣B/AML1 (Chen et al 1998). We also showed that the association of ␣B/AML1 with the nuclear matirix is essential for initiation of PyDNA replication (Chen et al 1998), and noted that, although many transcription factors are associated with the nuclear matrix, they are not always located in the same compartment.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation